Lure of the supreme joy: pedagogy and environment in the Neo-Confucian academies of Zhu Xi - Conan-Wu, Xin (Sinica Leidensia, 2024)
In this book, Xin Conan-Wu presents a radically revisionist analysis on Zhu Xi's (1130-1200) Neo-Confucian philosophy of education. She argues that landscape and poems in twelfth-century academies bespeak his natural pedagogy and reveal unsuspected contributions to Chinese cultural sensibility by this emblematic figure of a stultifying orthodoxy.